Impact of geography on prognostic outcomes of 21, 509 patients with metastatic colorectal cancer enrolled in clinical trials: an ARCAD database analysis. (June 2021) - Yin, Jun; Dawood, Shaheenah; Cohen, Romain; Meyers, Jeff; Zalcberg, John; Yoshino, Takayuki; Seymour, Matthew; Maughan, Tim; Saltz, Leonard; Van Cutsem, Eric; Venook, Alan; Schmoll, Hans-Joachim; et al.
Background: Benchmarking international cancer survival differences is necessary to evaluate and improve healthcare systems. Our aim was to assess the potential regional differences in outcomes among patients with metastatic colorectal cancer (mCRC) participating in international randomized clinical trials (RCTs). Design: Countries were grouped into 11 regions according to the World Health Organization and the EUROCARE model. Meta-analyses based on individual patient data were used to synthesize data across studies and regions and to conduct comparisons for outcomes in a two-stage random-effects model after adjusting for age, sex, performance status, and time period. We used mCRC patients enrolled in the first-line RCTs from the ARCAD database, which provided enrolling country information. There were 21, 509 patients in 27 RCTs included across the 11 regions. Results: Main outcomes were overall survival (OS) and progression-free survival (PFS). Compared with other regions, patients from the United Kingdom (UK) and Ireland were proportionaly over-represented, older, with higher performance status, more frequently male, and more commonly not treated with biological therapies. Cohorts from central Europe and the United States (USA) had significantly longer OS compared with those from UK and Ireland ( p = 0.0034 and p < 0.001, respectively), with median difference of 3–4 months. The survival deficits in the UK and Ireland cohorts were, at most, 15% at 1 year. No evidence of a regional disparity was observed for PFS. Among those treated without biological therapies, patients from the UK and Ireland had shorter OS than central Europe patients ( p < 0.001). Conclusions: Significant international disparities in the OS of cohorts of mCRC patients enrolled in RCTs were found. Survival of mCRC patients included in RCTs was consistently lower in the UK and Ireland regions than in central Europe, southern Europe, and the USA, potentially attributed to greater overall population representation, delayed diagnosis, and reduced availability of therapies.